A new model for renewal of business processes in innovative enterprises - Hustič, Igor (Naše gospodarstvo, 2009)
The transition from the routine-loving to the innovative society requires a permanent effort aimed at renewal of business processes for enterprises to practice innovative business and therefore attain competitiveness in contemporary global markets. For the effort to yield success, it must be clear what this means and which methods are suitable. An overview shows that none of the best known international methods has been found successful forever but rather temporarily. They must have some deficiencies. First of all, they are not requisitely holistic. Hence we suggest here a new model for renewal of business processes in highly innovative enterprises. It is based on a synergy of the most usable methods attained by systemic thinking.
Keywords: management; podjetja; vodenje; poslovni proces; prenova; reorganizacija; inovativno poslovanje; konkurenčnost